Daptomycin Resistant Staphylococcus aureus Clinical Strain With Novel Non-synonymous Mutations in the mprF and vraS Genes: A New Insight Into Daptomycin Resistance - Sabat, Artur J. (Front Microbiol, 2018)
Objectives: Daptomycin (DAP) resistance in Staphylococcus aureus is uncommon but there are increasing reports of the emergence of resistance during DAP therapy. Most clinical DAP-resistant S. aureus isolates investigated carried mutations in the mprF gene. The aim of this study was to identify mutations between a clinical pair of methicillin-susceptible S. aureus (MSSA) isolates (DAP-susceptible and DAP-resistant). Additionally, the activity of genes previously associated with DAP resistance was assessed. Materials and Methods: Two MSSA isolates from patient with left-sided endocarditis were analyzed by whole genome sequencing (WGS) and reverse transcription-quantitative real-time PCR (RT-qPCR). The first isolate, DAP-susceptible, was obtained before initiation of treatment and the second isolate, DAP-resistant, was recovered after 4 weeks of DAP therapy. Results: Comparison of complete genomes of DAP-susceptible and its DAP-resistant variant identified two non-synonymous and one synonymous mutations. The non-synonymous mutations consisted of a S829L substitution in mprF and a T331I substitution in vraS. The RT-qPCR experiments revealed an increased expression of vraS, dltA, mprF, and sceD genes in DAP-resistant variant. Strikingly, the expression of dltA and mprF genes was significantly downregulated by DAP. Conclusion: The mprF and vraS genes were previously associated with DAP resistance, however, none of the mutations described in this study had been previously identified and linked to DAP resistance. Moreover, we provide a new insight into the DAP action on S. aureus, in which the expression of key genes in DAP resistance is decreased by the antibiotic.